2011
DOI: 10.3989/scimar.03381.16e
|View full text |Cite
|
Sign up to set email alerts
|

Cnidom analysis combined with an in vitro evaluation of the lytic, cyto- and neurotoxic potential of <i>Cyanea capillata</i> (Cnidaria: Scyphozoa)

Abstract: SUMMARY:The cnidocysts and the lytic, cyto-and neurotoxic potency of a large specimen of Cyanea capillata (L.) with 55 cm umbrella diameter were compared with those of a pooled C. capillata sample (average ø 14 cm) in order to investigate organismal developments at a cellular and biochemical level. Nematocysts of the type A-isorhiza in both fishing tentacles and oral arms and the O-isorhizas of oral arms were enlarged in the 55 cm specimen. Additionally, the number of nematocysts per battery in the fishing ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…However, precise quantification of nematocyst discharge in response to test solutions proved difficult given the complexity of the Cyanea cnidome, which consists of euryteles, birhopaloids and three different isorhizas—a-isorhizas, A-isorhizas, and O-isorhizas—each with multiple size classes [ 37 ] ( Figure 1 ). It is essential to distinguish these types when evaluating discharge because studies have demonstrated that different nematocysts can vary not only in their morphology and penetrant abilities but also in their toxic effects [ 38 , 39 , 40 ]. However, precise quantification of percent discharge for each nematocyst type and size class was not possible with the microscope and camera available for this study; best efforts were made to identify cnidae types based on [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, precise quantification of nematocyst discharge in response to test solutions proved difficult given the complexity of the Cyanea cnidome, which consists of euryteles, birhopaloids and three different isorhizas—a-isorhizas, A-isorhizas, and O-isorhizas—each with multiple size classes [ 37 ] ( Figure 1 ). It is essential to distinguish these types when evaluating discharge because studies have demonstrated that different nematocysts can vary not only in their morphology and penetrant abilities but also in their toxic effects [ 38 , 39 , 40 ]. However, precise quantification of percent discharge for each nematocyst type and size class was not possible with the microscope and camera available for this study; best efforts were made to identify cnidae types based on [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we noted that vinegar does not equally induce discharge in all nematocyst types, and did not elicit as much discharge as other solutions (urine, isopropanol). It is not known how each nematocyst type contributes to toxicity, but previous studies have suggested that the largest A-isorhizas and O-isorhizas disproportionately contribute to hemolysis [ 40 ], and these cnidae types were not triggered by vinegar application. Thus, it may be that vinegar does not induce discharge of the most toxic types of nematocysts, and that any discharge that occurs during the rinsing process does not contribute measurably to hemolytic activity, the functional metric of our venom activity assays.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cytotoxicity has been reported for C. capillata and A. aurita using RTgill‐W1 cell lines (Helmholz et al., ). The fishing tentacles contain predominantly A‐isorhiza and O‐isorhiza nematocysts, whereas the oral arms dominate in O‐isorhizas (Helmholz et al., ). However, the number, size and potency of the venom contained in these different types of nematocysts vary with jellyfish size and geographical location (Helmholz et al., ; Wiebring et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…As the jellyfish become trapped on the outside of the net cage, they break apart and pieces pass through into the cage. The tentacles, be they the fishing tentacles, mesenteric tentacles, oral arms or exumbrella all contain A‐, O‐ and a‐isorhizas and eurytales nematocysts although the number and characteristics of each type can vary by size and geographic location (Helmholz et al., ; Wiebring, Helmholz, Lassen, Prange, & Jarms, ). The gill cell toxicity of the venom from C. capillata and A. aurita has been examined in vitro using RTgill‐W1 cells (Helmholz, Johnston, Ruhnau, & Prange, ); however, these assays do not demonstrate the pathological effects on envenomated fish.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the erythrocyte lysis (HE 50 ) induced by crude venom from mesenteric tentacles of large jellyfish was greater (98 μg/mL) than that induced from small medusae extracts (177 μg/mL). Therefore, the size of fishing tentacles and of oral arms, and nematocyst (A-isorhizas and O-isorhizas) number and size that correspond to the size of umbrella, were correlated with the cytolytic potency in differently-sized Cyanea capillata (L.) showing that the greater the specimen, the higher the produced hemolysis [ 47 ]. A concentration-dependent increase of hemolysis induced by extracts from Cyanea capillata tentacles was observed also in rat erythrocytes in the presence of Ca 2+ ; this increase was attenuated by Ca 2+ channel blockers such as Diltiazem, Verapamil and Nifedipine [ 48 ].…”
Section: Hemolytic Effects Of Cnidarian Venomsmentioning
confidence: 99%